Innovative Tools and Techniques as a Factor Supporting Small and Medium Enterprises in the Agri-Food Sector - Sebastian Jarzębowski; Natalia Bezat (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The goal of the paper was to focus on the agri-food sector from a perspective of innovation. In the article, the current situation related to innovative tools and techniques identified in the agri-food sector was presented. The attention was focused on the benefits resulting from the application of innovative solutions in three areas: food safety, mechatronics, and packaging design. The empirical part of the paper includes a description and a summary of case studies on innovations implementations conducted within the framework of the Interreg I-CON project.